Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe TGT (Team Games Tournamen) Terhadap Peningkatkan Minat Belajar Siswa - Asri Fuji Rahayu; Uus Manzilatusifa; Cucu Lisnawati (Jurnal Pendidikan dan Pembelajaran Ekonomi Akuntansi, 2018)
This research is motivated by the low learning interest of students in economic subjects. The efforts of teachers in carrying out learning activities at this time have not been oriented towards increasing students' interest in learning. Based on these problems, it is necessary for new innovations in learning that aim to find a learning model that is suitable to increase students' learning interest, namely the Teams Games Tournament (TGT) cooperative learning model. The purpose of this study was to determine the application and influence of the team game tournament learning model on the learning interest of students in the eleventh grade of IIS 1. This study was an experimental study that was quantitative. Based on the results of data analysis shows that there are differences in learning interests of students between the control class and the experimental class with the treatment model of Teams Games Tournament learning. The average learning interest of students in the experimental class is 38.49 and the control class is 30.27. Therefore, it can be said that the application of the Cooperative Teams Games Tournament type learning model can significantly influence students' learning interest in economic subjects.